Challenges in peer review in Nepali medical journals - Koirala, Dipti; Adhikari, Bibhav (Journal of Gandaki Medical College-Nepal, 2025)
Peer review remains the cornerstone of quality assurance in scientific publishing, yet its effective implementation faces unique obstacles in resource-limited settings. In Nepal, rapid growth in medical research output, coupled with a small pool of experienced reviewers and rising submission volumes, has strained the peer-review system of local journals. Key challenges include a limited number of qualified reviewers (only ~1,800–2,000 active health-science researchers with h-index ≥1 serving >70 journals), widespread lack of formal reviewer training, reliance on manual editorial processes, intense pressure from academic promotion criteria, and frequent institutional conflicts of interest. These factors contribute to prolonged review times (median 118–124 days), high reviewer refusal rates, and occasional compromises in rigour. Strengthening peer review in Nepal requires a coordinated national effort: standardized and transparent processes, structured reviewer training and mentorship programmes, wider adoption of online journal systems, public recognition or continuing medical education credits for reviewers, and cultivation of peer review as an integral component of scientific citizenship. Addressing these bottlenecks is essential to enhance the credibility, efficiency, and global visibility of Nepalese medical journals.